(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The importance of the research is that it is a research attempt that is concerned with consolidating the ideaof a pressing play style in the reality of Iraqi clubs and teams training through this defensive method toachieve the desired goal, as well as experimenting with the use of defensive exercises characterized by rapidapplication and high accuracy together, and to know the extent of the impact of exercises in a pressing styleof play in developing defense man to man for young football players in a step aimed at strengthening thesports field with practical experiments and service to researchers in the sports field. The research objectivesto prepare pressing play style exercises to develop defense, man to man, for young football players. Toidentify the effect of exercises in a pressing play style in developing defense, man to man for young footballplayers. The researchers used the experimental method to design the two equivalent groups (experimentaland control) with a pre and post- test that is consistent with the nature of the research problem. The researchsample was chosen by a simple random method (lottery), where the experimental group was represented bythe Al Shuohda youth sports club, whose number was (22) players, and the control group was represented inthe Nahrain youth sports club, whose number is (21), (10) players were chosen from each group, experimentaland control group by the deliberate method, and the research variables included the defense man to man(Close defense - flexible defense - cutting and acquisition - cutting and farthest). The researchers usedstatistical methods (mean, standard deviation, coefficient of torsion, Levin’s coefficient, t-test for correlatedand non-correlated samples), and after presenting, analyzing and discussing the results, the researchersreached the following conclusions: pressing play style exercises developed man-to-man defense with twotypes of close defense and flexible defense for the experimental group under study. pressing play developedcutting, possession, cutting and farthest.